Meninjau Kembali Hadis "Yassiru wa La Tuassiru, Bashshiru wa La Tunaffiru": Paradigma Profetik untuk Deradikalisasi Keagamaan di Indonesia - Rahman; Ghozali, Achmad; Darussamin, Zikri; Suhaimi; Usman (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
Religious radicalism often arises from rigid and literalist interpretations of Islamic sources that overlook the Prophetic values of mercy (rahmah), facilitation (taysir), and moderation. This article revisits the hadith "Yassiru wa la tuassiru, bashshiru wa la tunaffiru" ("Make things easy and do not make them difficult; give glad tidings and do not drive people away") as a normative and strategic framework for religious deradicalization in Indonesia. Using qualitative library research, the study examines the hadith through takhrij, sanad and matn analysis, asbab al-wurud, and classical and contemporary commentaries. The findings show that facilitation (taysir), encouragement (tabshir), and avoiding deterrence (tanfir) form a coherent paradigm to counter extremism by promoting inclusive, tolerant, and humanistic religiosity. Applied in education, dawah, and public policy, this Prophetic ethic strengthens religious moderation, prevents radicalization, and supports social harmony.